Targeting the Aspergillus flavus p2c gene through host-induced gene silencing reduces A. flavus infection and aflatoxin contamination in transgenic maize - Raruang, Yenjit; Omolehin, Olanike; Hu, Dongfang; Wei, Qijian; Promyou, Surassawadee; Parekattil, Lidiya J.; Rajasekaran, Kanniah; Cary, Jeffrey W.; Wang, Kan; Chen, Zhi-Yuan (Frontiers in Plant Science, 2023)
Aspergillus flavus is an opportunistic fungal pathogen that infects maize and produces aflatoxins. Using biocontrol or developing resistant cultivars to reduce aflatoxin contamination has only achieved limited success. Here, the A. flavus polygalacturonase gene (p2c) was targeted for suppression through host-induced gene silencing (HIGS) to reduce aflatoxin contamination in maize. An RNAi vector carrying a portion of the p2c gene was constructed and transformed into maize B104. Thirteen out of fifteen independent transformation events were confirmed to contain p2c. The T2 generation kernels containing the p2c transgene had less aflatoxin than those without the transgene in six out of eleven events we examined. Homozygous T3 transgenic kernels from four events produced significantly less aflatoxins (P ≤ 0.02) than the kernels from the null or B104 controls under field inoculation conditions. The F1 kernels from the crosses between six elite inbred lines with P2c5 and P2c13 also supported significantly less aflatoxins (P ≤ 0.02) than those from the crosses with null plants. The reduction in aflatoxin ranged from 93.7% to 30.3%. Transgenic leaf (T0 and T3) and kernel tissues (T4) were also found to have significantly higher levels of p2c gene-specific small RNAs. Further, homozygous transgenic maize kernels had significantly less fungal growth (27~40 fold) than the null control kernels 10 days after fungal inoculation in the field. The calculated suppression of p2c gene expression based on RNAseq data was 57.6% and 83.0% in P2c5 and P2c13 events, respectively. These results indicate clearly that the reduced aflatoxin production in the transgenic kernels is due to RNAi-based suppression of p2c expression, which results in reduced fungal growth and toxin production.